(untitled) (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Plica Polonica or Polish plait is a rare condition characterized by tangling and matting of hair that can lead to secondary infections. It has been reported globally with various etiologies including psychiatric illness and pathophysiology involves longitudinal splitting of hair often leading to complications. This study aimed analyze an unusual case of acute-onset Plica Polonica following shampoo application, highlighting the importance of recognizing non-psychiatric triggers. Presentation of Case: A 25-year-old female presented with sudden hair matting within minutes of shampoo application, exhibiting characteristic "bird’s nest" appearance without evidence of infection or infestation. The patient had no history of psychiatric illness or other comorbidities. Discussion: While Plica Polonica is commonly associated with psychiatric conditions and self-neglect, this case demonstrates an acute presentation triggered by shampoo use. The pathophysiology may involve alterations in hair shaft bonds leading to matting. Conclusion: This case highlights the importance of considering external triggers in Plica Polonica, beyond the traditional associations with psychiatric conditions and self-neglect. Early recognition and appropriate management are crucial for preventing complications.